Utilizing ArchivesSpace for Data Archiving: A Case Study of the Digital Archive for Ethnological and Anthropological Resources at the Institute of Ethnology and Anthropology - Crvenkovska Risteska, Ines; Risteski, Ljupcho (Ethnographica et Folkloristica Carpathica, 2025)
The purpose of this paper is to present and promote the positive experiences of the Institute of Ethnology and Anthropology in utilizing ArchivesSpace – an open-source web-based database management application that facilitates access, description, and arrangement of processed materials, including analog, hybrid, and newly created digital content. These materials are effectively represented through a public user interface and can be used across the domains of library, archival, and museum work. By focusing on the implementation and use of ArchivesSpace within the institute, this study underscores its potential as a sustainable solution for heritage institutions that seek to manage, preserve, and present their cultural resources in an efficient and accessible manner. The paper highlights the software’s advantages, such as its open-source nature, adaptability, and capacity to handle various forms of materials, emphasizing its contribution to enhancing the visibility of cultural heritage and improving its accessibility for diverse audiences. Furthermore, this research reflects on the benefits of using ArchivesSpace in contexts that face financial and infrastructural limitations, illustrating how it can empower institutions with limited resources to digitize and preserve their collections while ensuring they remain publicly accessible. The paper concludes by encouraging other institutions, especially those in countries with emerging digital preservation strategies, to explore the potential of ArchivesSpace to support their archival and cultural heritage management needs.